Deiksis Waktu dan Ruang Dalam Surat Al-Waqiah (International Forum of Researchers and Lecturers, 2023)
Language is the most important means of communication. Language also has scientific value, one of the studies of linguistics or linguistics is pragmatics. The discussion of pragmatics examines deixis, where a word has a meaning to refer to the meaning of something that has existed before. Deixis is a phenomenon in which contextual information is identified by lexical forms or grammatical distinctions, information that becomes clear only when linked to context. Phenomena involving phrases that cannot be separated from their context are called deictic expressions. Meanwhile, several linguistic forms used to indicate something are called deictic. Al-Qur'an is a book that contains a very deep meaning and has even been studied further. Based on semantic studies, the Qur'an contains words that are full of meaning. In this context, the researcher conducted his research on Surah Al Waqi'ah and focused on the study of time and space deixis.